Logic – How to Derive Rules for Existential Quantifiers from Universal Quantifiers

logic

An instructive exercise, given the negation rules for classical logic, is to show that the rules for ∃ (for ∀) are derivable from the rules for ∀ (for ∃) and the definition of ∃x(A(x)) as ¬∀x¬(A(x)) (the definition of ∀x(A(x)) as ¬∃x¬(A(x)))

What am I supposed to do here exactly? Assume that the rules for $\forall$ are true, and that $\exists x(A(x))\Leftrightarrow\neg\forall x\neg(A(x))$?

But what do I prove? How can I prove that some rule can be inferred from another rule without assuming that the to-be-proved rule is true?

Im not asking for a solution, i just want to understand what it's asking me to do.

Here are the rules:
enter image description here

enter image description here

enter image description here

Best Answer

tl;dr In the first section I explain what you need to do. In the second section I explain the importance of doing this. Since you didn't want to see the solution, in the third section I give the solution of a similar (but not identical) example problem.


I. The existential quantifier satisfies two rules. The first is existential introduction $\exists$-I, which allows you to start from the premise $A(t)$, and arrive at the conclusion $\exists x. A(x)$.

The exercise is asking you to show that you can still do the same thing if you have $\neg\forall\neg$ in place of $\exists$: i.e., you can start from the premise $A(t)$, and eventually arrive at the conclusion $\neg\forall x.\neg A(x)$, while using only the rules of the universal quantifier ($\forall$-I, $\forall$-E) and the negation connective ($\neg$-I and some classical rule, probably $\neg\neg$-E) at each step.

Similarly, to prove that the $\exists$-E rule is derivable from the rules of the universal quantifier and the rules of negation, you will need to show that starting from $\neg \forall x.\neg A(x)$ and a subproof deducing $C$ from $A(a)$, you can conclude $C$ using only the rules of the universal quantifier and the negation connective at each step.


II. Why does this matter? Because it allows you to eliminate the use of the existential quantifier from every proof/derivation: first you replace $\exists x. A(x)$ with $\neg\forall x.\neg A(x)$ throughout the derivation (which breaks the proof since the rules you apply are no longer valid), then replace each use of the $\exists$-I/E rule with a sequence of $\forall$-I/E and $\neg$-I/E rules (thus repairing the proof).


III. a. Since you don't want to see a solution, let me solve a similar example problem instead.

The introduction rule $\vee$-I1 states that from $P$ you can derive $P \vee Q$. I will show that given the classical rules for $\neg$, the $\vee$-I1 rule is derivable from the rules of $\wedge$, by defining $P \vee Q$ as $\neg (\neg P \wedge \neg Q)$.

The $\vee$-I1 rule lets us start from $P$, and allows us to conclude $P \vee Q$. So we need to show that we can start from $P$, and using only the rules $\wedge$-I/E1/E2, $\neg$-I and $\neg\neg$-E, we can conclude $\neg (\neg P \wedge \neg Q)$.

So start from $P$. Assume $\neg P \wedge \neg Q$. From this assumption, we can get $\neg P$ by $\wedge$-E1. We now have both $P$ and $\neg P$, a contradiction. By $\neg$-I, we can now discharge the assumption $\neg P \wedge \neg Q$ and conclude $\neg (\neg P \wedge \neg Q)$. This is what we had to show: starting from $P$, we concluded $\neg (\neg P \wedge \neg Q)$, using only the rules of $\wedge$ and $\neg$.

III. b. The elimination rule $\vee$-E states that starting from $P \vee Q$, and two subproofs, one deducing $C$ from the assumption $P$, and another deducing $C$ from the assumption $Q$, we can deduce $C$.

I will now show that starting from $\neg (\neg P \wedge \neg Q$), and given two subproofs, one deducing $C$ from the assumption $P$, and another deducing $C$ from the assumption $Q$, we can deduce $C$ using only the classical rules for $\neg$ and $\wedge$.

Call the given subproof deducing $C$ from the assumption $P$ "subproof 1". Similarly, call the subproof deducing $C$ from the assumption $Q$ "subproof 2".

Start from $\neg (\neg P \wedge \neg Q)$. Assume $\neg C$.

Assume $P$. Copy subproof 1 below this assumption to deduce $C$. This contradicts our assumption of $\neg C$, so we can use $\neg$-I to discharge the assumption $P$ and conclude $\neg P$.

Now assume $Q$. Copy subproof 2 below this assumption to deduce $C$. This contradicts our assumption of $\neg C$, so we can use $\neg$-I to discharge the assumption $Q$ and conclude $\neg Q$.

We have derived $\neg P$ and $\neg Q$ above. So we can use $\wedge$-I to deduce $\neg P \wedge \neg Q$. But this contradicts our starting point $\neg (\neg P \wedge \neg Q)$. Therefore, we can use $\neg$-I to discharge the assumption $\neg C$ and get $\neg \neg C$. Finally, we can apply the classical rule $\neg\neg$-E to get $C$, as desired.

Related Question